Construction of covalent organic framework with unique double-ring pore for size-matching adsorption of uranium. Issue 47 (9th December 2020) - Zhang, Jie; Zhou, Lihong; Jia, Zhimin; Li, Xiaofeng; Qi, Yue; Yang, Chuting; Guo, Xinghua; Chen, Shanyong; Long, Honghan; Ma, Lijian
Abstract : A new type of COF with a double-ring pore shows a size-matching adsorption effect for uranium with removal rate up to 99.8%. Abstract : The separation and recovery of key nuclides such as uranium and plutonium from effluents related to nuclear industry is of great significance for alleviating the shortage of nuclear energy resources and protecting the environment and human health. However, the high temperature, strong acidity and radioactivity of the nuclear effluents pose a severe challenge to the separation materials used in such conditions. The diversity of structure, flexibility of design, and excellent physicochemical stability of covalent organic framework materials (COFs) provide the possibility for the directional design and preparation of adsorbents for use under harsh conditions. Herein, three COFs with similar structure, different pore sizes and connecting modules were synthesized. The ingenious structure predesign enables Dp-COF to have three carboxyl groups oriented toward the pore center and laid out in appropriate spatial positions, which builds hydrogen-bonding bridges between carboxycarbonyl and hydroxyl groups, and thus constructs for the first time a unique COF material with a double-ring pore. The inner pore size of the "double-ring" is slightly larger than the diameter of uranyl hydrate, which leads to a size-matching adsorption of uranium by Dp-COF, thus greatly reducing the effect of protonation. Even in the simulated spent fuel reprocessing liquid with pH = 1.0, the adsorption capacity of Dp-COF for uranium can reach 66.3 mg g −1, and the adsorption capacity reaches 317.3 mg g −1 at pH = 4.5, which is very rare among the reported COFs. More excitingly, the removal rate for uranium reaches up to an unprecedented 99.8% due to the size-matching effect, more than any analogous adsorbents. This study not only proposes new ideas for the design and regulation of the microscopic configuration of COF materials, but also provides an alternative approach for the preparation of efficient uranium adsorbents.